In Vitro Microleakage of class V Composite Restorations prepared by Er,Cr:YSGG Laser and Carbide BUR - Synarellis Athanasios; Kouros Pantelis; Koulaouzidou Elisabeth; Strakas Dimitrios; Koliniotou-Koumpia Eugenia (Balkan Stomatological Society, 2017)
Background: The aim of this in vitro study was to compare the degree of microleakage on enamel and dentin margins of class V cavities prepared with either a high-speed drill or an Er,Cr:YSGG laser (2780 nm) and to associate their use with a beveling method for the margin.